An Approach to Reconciling Competing Ethical Principles in Aggregating Heterogeneous Health Preferences. (August 2017) - Dewitt, Barry; Davis, Alexander; Fischhoff, Baruch; Hanmer, Janel
Background. Health-related quality of life (HRQL) scores are used extensively to quantify the effectiveness of medical interventions. Societal preference-based HRQL scores aim to produce societal valuations of health by aggregating valuations from individuals in the general population, where each aggregation procedure embodies different ethical principles, as explained in social choice theory.Methods. Using the Health Utilities Index as an exemplar, we evaluate societal preference-based HRQL measures in the social choice theory framework.Results. We find that current preference aggregation procedures are typically justified in terms of social choice theory. However, by convention, they use only one of many possible aggregation procedures (the mean). Central to the choice of aggregation procedure is how to treat preference heterogeneity, which can affect analyses that rely on HRQL scores, such as cost-effectiveness analyses. We propose an analytical-deliberative framework for choosing one (or a set of) aggregation procedure(s) in a socially credible way, which we believe to be analytically sound and empirically tractable, but leave open the institutional mechanism needed to implement it.Conclusions. Socially acceptable decisions about aggregating heterogeneous preferences require eliciting stakeholders' preferences among the set of analytically sound procedures, representing different ethical principles. We describe a framework for eliciting such preferences for the creation of HRQL scores, informed by social choice theory and behavioral decision research.